A Helping Hand During Covid-19 Pandemic: Exploring Motivation and Implications Corporate Social Responsibility Banking Sector - Dewi, Kadek Goldina Putri; Sukoharsono, Eko Ganis; Baridwan, Zaki (Accounting Department,, 2022)
Purpose: This study explores the motivations and implications of implementing Corporate Social Responsibility in Bali's banking sector during the COVID-19 pandemic. Design/methodology/approach The methodology used in this research is qualitative research with a case study approach. Findings The study's results are that the motivation for implementing Corporate Social Responsibility during the COVID-19 pandemic is to comply with applicable norms/rules, caring attitudes, awareness, and social responsibility, as well as the company's desire to empower communities, get awards and fulfil social interests. Also, these study's findings are related to the implications of implementing Corporate Social Responsibility, namely improving the company's image, increasing customer trust, establishing better relationships with stakeholders, and transmitting kindness, gratitude, happiness, self-confidence, and respect. The concept of motivation and the implications of implementing Corporate Social Responsibility in Bali's banking industry, especially PT Bank Pembangunan Daerah Bali, during the Covid-19 pandemic, can be implemented in 3 forms of implementation, namely community relations, which are charity or donation activities, philanthropic community assistance. Or help partially solve problems and be citizenship-oriented to build community competitiveness. Practical implications This research encourages the development of socio-environmental accounting studies, and this research can provide input to the authorities in regulating policies or regulations regarding the importance of caring attitudes towards society and the environment and how the community has felt the impacts. Because, as we know, the Corporate Social Responsibility disclosure reporting policy is in the form of a sustainability report, which is still voluntary, it is hoped that the government can require disclosure of Corporate Social Responsibility reporting to large companies that have a relatively good financial performance by making standard reporting standards, accepted by the whole company because this sustainability report is the best means of providing information to investors and shareholders. Originality/value: This research framework is compiled from business people's aspirations, especially in the banking sector, who seek to foster motivation to care about the social and environmental environment by implementing Corporate Social Responsibility, which will have implications for corporate sustainability. Keywords Implementation; Corporate Social Responsibility; Charity; Philanthropy; Citizenship. Paper-type Case study